TIPOLOGI SOSIAL EKONOMI MASYARAKAT DALAM NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER - Hasbi, Nur; Nurrahma, Nurrahma; Musawir, Muhammad (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2024)
The focus of this study is to discuss the socio-economic typology of coastal and urban communities using a sociological literary approach. This study aims to describe the socio-economic typology of coastal and urban communities in Pramoedya Ananta Toer's novel Gadis Pantai. The method used in this study is a qualitative descriptive method. Data in the form of novel excerpts obtained, recorded and selected based on the problems discussed, namely describing socio-economic typology. The results of the study found three socio-economic typologies in coastal communities, namely: (1) the socio-economic typology of the upper class, the community included in this group, namely Bendoro and his family; (2) the socio-economic typology of the middle class, the community included in this group, namely Gadis Pantai, Mardinah, and Pelayan Tua; (3) the socio-economic typology of the lower class, the community included in this group, namely the coastal community, Bapak, Emak, and Dul.